The International Commercial Dispute Prevention and Settlement Organization: A Global Laboratory of Dispute Resolution with an Asian Flavor - Guiguo Wang; Rajesh Sharma (AJIL Unbound, 2021)
The Second Belt and Road Forum for International Cooperation announced the establishment of the International Commercial Dispute Prevention and Settlement Organization (ICDPASO) in 2019. The ICDPASO was coordinated by the China Council for the Promotion of International Trade and the China Chamber of International Commerce, together with industrial and commercial organizations and legal service agencies from over thirty countries and regions including the European Union, Italy, Singapore, Russia, Belgium, Mexico, Malaysia, Poland, Bulgaria, and Myanmar. It was launched on 15 October 2020. As its title indicates, ICDPASO's mandate to provide dispute resolution services is not confined to the Belt and Road Initiative (BRI) countries but includes resolving any disputes that the parties entrust to its jurisdiction. The ICDPASO aims to serve as a “legal hub” to resolve commercial and investment disputes effectively, efficiently, and practically. Unlike other multilateral dispute resolution forums, it is intended to provide an Asian-centric multilateral dispute resolution forum. This essay, the first on the subject of the ICDPASO, discusses how the ICDPASO can serve as a global laboratory for experimenting and innovating in dispute resolution with the potential to impact the landscape of international law, in particular its innovative use of mediation, good offices, and appeal processes to prevent and resolve disputes arising from the BRI. As BRI projects aim to establish infrastructure and digital connectivity within BRI countries and regions for trade and development, this essay argues that the dispute resolution process under the ICDPASO should take into account the overall development of a country or region. The essay concludes that the ICDPASO will be a game changer by introducing an Asian way of resolving disputes.